Articulations of Self and Politics in Activist Discourse : A Discourse Analysis of Critical Subjectivities in Minority Debates - Zienkowski, Jan (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book focuses on the discursive processes that allow activists to make sense of themselves and of the modes of politics they engage in. It shows how political and metadiscursive awareness develop in tandem with a reconfiguration of one's sense of self. The author offers an integrated pragmatic and poststructuralist perspective on self and subjectivity. He draws on Essex style discourse theory, early pragmatist philosophy, and linguistic pragmatics, arguing for a notion of discourse as a multi-dimensional practice of articulation. Demonstrating the analytical power of this perspective, he puts his approach to work in an analysis of activist discourse on integration and minority issues in Flanders, Belgium. Subjects articulate a whole range of norms, values, identities and narratives to each other when they engage in political discourse. This book offers a way to analyse the logics that structure political awareness and the associated boundaries for discursive self-interpretation.
Keywords: Linguistics.; Europe -- Politics and government.; Germanic languages.; Sociolinguistics.; Discourse analysis.; Pragmatics.; Sociology.; elektronické knihy; electronic books